Aroma sebagai Komunikasi Artifaktual Pencetus Emosi Cinta: Studi Olfactics pada Memory Recall Peristiwa Romantis - Wahyuningtyas, Bhernadetta Pravita (Bina Nusantara University, 2015)
This study describes how scents can be a trigger for the memories about relationships. Scents inhaled do not only awaken a person's thoughts and feelings about the beautiful and fun memories in the past, but can trigger emotions also, especially the emotion of love ending up in miserable way, without power to strengthen it. Change is constant, as well as scent, its existence can always be a trigger of the emotional memories of love that is still tethered. Scents send specific messages of communication. They are associated with attraction and often trigger emotional romantic feelings. What can be triggered by scent or what sort of emotions that can be caused by a particular scent really depends on the experience, memories, and, to some extent, cultural background because every culture has various mapping on scent. Scent is closely linked to perception. In communications, scent is classified as artifactual communication or nonverbal communication. Olfactics or olfactory communication, or the study of scent is very important in a variety of communication situations. Olfactics in communications is to attract people's attention, to complement the flavors and tastes, to recall the events of emotional situations, and to form an image of one self and identity. Scents specifically trigger the memories of romantic feelings and affect a person’s feelings. This study analyzed the love relationships experienced by informants who have had romantic relationship for at least one year. The paradigm used in this study is positivism, with descriptive qualitative approach. Data collection techniques are in-depth interview and observation.